Age of Acquisition Modulates Alpha Power During Bilingual Speech Comprehension in Noise - Grant, Angela M.; Kousaie, Shanna; Coulter, Kristina; Gilbert, Annie C.; Baum, Shari R.; Gracco, Vincent; Titone, Debra; Klein, Denise; Phillips, Natalie A. (Frontiers in Psychology, 2022)
Research on bilingualism has grown exponentially in recent years. However, the comprehension of speech in noise, given the ubiquity of both bilingualism and noisy environments, has seen only limited focus. Electroencephalogram (EEG) studies in monolinguals show an increase in alpha power when listening to speech in noise, which, in the theoretical context where alpha power indexes attentional control, is thought to reflect an increase in attentional demands. In the current study, English/French bilinguals with similar second language (L2) proficiency and who varied in terms of age of L2 acquisition (AoA) from 0 (simultaneous bilinguals) to 15 years completed a speech perception in noise tasks. Participants were required to identify the final word of high and low semantically-constrained auditory sentences such as "Stir your coffee with a spoon" vs. "Bob could have known about the spoon" in both of their languages and in both noise (multi-talker babble) and quiet during electrophysiological recording. We examined the effects of language, AoA, semantic constraint, and listening condition on participants’ induced alpha power during speech comprehension. Our results show an increase in alpha power when participants were listening in their L2, suggesting that listening in an L2 requires additional attentional control compared to the first language, particularly early in processing during word identification. Additionally, despite similar proficiency across participants, our results suggest that under difficult processing demands, AoA modulates the amount of attention required to process the second language.